Determinants of long‐term paramagnetic rim lesion evolution in people with multiple sclerosis - Jack A. Reeves; Alexander Bartnik; Maryam Mohebbi; Murali Ramanathan; Niels Bergsland; Dejan Jakimovski; Gregory E. Wilding; Fahad Salman; Ferdinand Schweser; Bianca Weinstock‐Guttman; David Hojnacki; Svetlana Eckert; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Baseline paramagnetic rim lesion (PRL) load predicts disease progression in people with multiple sclerosis (pwMS). Understanding how PRLs relate to other known MS‐related factors, and the practical utility of PRLs in clinical trials, is crucial for informing clinical decision‐making and guiding development of novel disease‐modifying treatments (DMTs). Methods This study included 152 pwMS enrolled in a larger prospective, longitudinal cohort study who had 3T MRI scans and clinical assessments at baseline and 5‐ or 10‐year follow‐ups. PRLs were identified on baseline 3T quantitative susceptibility maps and classified as persisting, disappearing, or newly appearing at follow‐up. The relationships between PRL evolution and clinical, radiological, environmental, and genetic characteristics were assessed, and clinical trial sample sizes were estimated using PRL appearance or disappearance as outcome measures. Results DMT use was associated with lower odds of new PRL appearance (for high‐efficacy DMTs: odds ratio = 0.088, p = 0.024), but not disappearance. Current smoking status was associated with greater baseline PRL number (B = 0.527 additional PRLs, p = 0.013). A 24‐month clinical trial in people with progressive MS for a DMT that doubles the rate of PRL rim disappearance would require an estimated 118 people with progressive MS per group at 80% statistical power. Interpretation Early MS diagnosis and subsequent DMT initiation may reduce new chronic active inflammation. However, the utility of PRL disappearance or new PRL appearance as outcome measures in clinical trials is limited by potentially large sample sizes that are needed for moderate efficacy drugs.